A Literature Review on Social and Economic Factors Related to Access to Dental Care for Pregnant Women - Ojeda, Jairo Corchuelo (The Journal of Dentists, 2013)
Background: The early detection of oral pathology in the pregnant woman can contribute to reduction in childbirth-related complications and consequences of low birth weight. The purpose of this review was to identify and analyze main social and economic factors related to access to dental care of pregnant women. Methods: The Guide on implementation of the narrative synthesis was used systematic reviews of research evidence Popay et al. 2006. The review process included identification of the approach to review, search and allocation of the available evidence, review question was specified, identified studies for inclusion in the review, extracted data and evaluation of the quality of the study. The search was about pregnant women and dental services. Qualitative and quantitative studies in a period from 1990 to 2013 were included. Publications included are in English, Portuguese and Spanish. Age was women over the age of 13 and under 45 years of age. Results: Of 120 relevant items found in electronic databases used as PubMed, library virtual em Saúde, ISI Web of Knowledge, Scielo, The Anthropological Index Online, PsycInfo, The Psychology & Behavioral Sciences Collection, SocINDEX, ProQuest, network of scientific journals of Latin America and the Caribbean, Spain and Portugal, EBSCO, Google school. Only thirty-three articles satisfied the quality criteria to be included in the review. The most frequently identified relating to access to dentistry-related factors were: age of the pregnant woman, schooling level, ethnicity, marital status, income, occupation, socioeconomic level and attention-related social dynamics as access to information, health assurance and use of dental service according to trimester of gestation. This review found that the level of schooling achieved, family income, the marital status and having health insurance were important predictors of attending for dental care. Only three articles were qualitative research. Conclusions: The existence of published reports on the topic of search suggests the need for more qualitative and quantitative research. Actions to improve the coverage and dental care of pregnant women should consider social and economic factors and not just the change in user behavior.